2017
DOI: 10.1016/j.drugalcdep.2017.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and substance use diagnoses among HIV-positive patients receiving care in NYC clinic settings

Abstract: Background Substance use among HIV-positive persons exacerbates health problems. This study sought to estimate the prevalence of alcohol and drug-use diagnoses and examined hypothesized predictors associated with alcohol and drug-use diagnoses among HIV-positive patients in New York City (NYC). Methods This cohort study reviewed electronic medical records (EMRs) of 4,965 HIV-positive patients based on diagnostic codes. These patients attended a comprehensive care clinic in NYC in 2012. Multinomial logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Age, race, gender, income, education, polysubstance use, visit number, and visit type were assessed as potential correlates of validity based on prior literature showing associations between these characteristics and validity of self-reported substance use in different settings (Fendrich, Mackesy-Amiti, & Johnson, 2008; Langendam, van Haastrecht, & van Ameijden, 1999; Rendon et al, 2017; Schuler, Lechner, Carter, & Malcolm, 2009; White et al, 2014). Sexual orientation, HIV status, and depression were included as exploratory candidates based on elevated rates of substance use among sexual minorities (Medley et al, 2016), HIV-positive individuals (Gurung et al, 2017), and those suffering from depression (Swendsen & Merikangas, 2000), which make the validity of self-reported substance use among these groups of particular interest.…”
Section: Methodsmentioning
confidence: 99%
“…Age, race, gender, income, education, polysubstance use, visit number, and visit type were assessed as potential correlates of validity based on prior literature showing associations between these characteristics and validity of self-reported substance use in different settings (Fendrich, Mackesy-Amiti, & Johnson, 2008; Langendam, van Haastrecht, & van Ameijden, 1999; Rendon et al, 2017; Schuler, Lechner, Carter, & Malcolm, 2009; White et al, 2014). Sexual orientation, HIV status, and depression were included as exploratory candidates based on elevated rates of substance use among sexual minorities (Medley et al, 2016), HIV-positive individuals (Gurung et al, 2017), and those suffering from depression (Swendsen & Merikangas, 2000), which make the validity of self-reported substance use among these groups of particular interest.…”
Section: Methodsmentioning
confidence: 99%
“…Both unemployment and educational level are linked to a higher socioeconomic status, which may indicate better access to health care and to nutritious food. Substance use (e.g., marijuana, alcohol, methamphetamine, cocaine, and others) among PLHIV also seems to be an important moderator of sarcopenia, perhaps directly or indirectly through suboptimal adherence to ARV [61,62] Furthermore, several bone-related abnormalities (i.e., low bone mineral density, osteoporosis, osteopenia, osteomalacia, and fractures) have been observed in PLHIV, likely influenced by both HIV, lifestyle factors, and ART [63].…”
Section: Traditional and Hiv-related Risk Factors Contribute To The Dmentioning
confidence: 99%
“…54,55 The study of hazardous alcohol use is especially important because of the deleterious effects on immune functioning caused by alcohol use, 56 which could increase the risk for HIV-seroconversion with inadequate PrEP adherence. One study of GBM in Atlanta found that 75% endorsed beliefs that alcohol had interactive toxicity effects with anti-retroviral medications; however, the study did not investigate if GBM purposefully missed PrEP doses timed around binge drinking events.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to club drugs, heavy alcohol use results in behavioral disinhibiting effects; 50 hazardous alcohol use has been associated with greater CAS among GBM 51 and lower HIV mediation adherence among samples of persons living with HIV including GBM, 52,53 particularly when used in combination with other drugs. 54,55 The study of hazardous alcohol use is especially important because of the deleterious effects on immune functioning caused by alcohol use, 56 which could increase the risk for HIV-seroconversion with inadequate PrEP adherence. One study of GBM in Atlanta found that 75% endorsed beliefs that alcohol had interactive toxicity effects with anti-retroviral medications; however, the study did not investigate if GBM purposefully missed PrEP doses timed around binge drinking events.…”
Section: Introductionmentioning
confidence: 99%